Are we shortchanging frail older people when it comes to the pharmacological treatment of urgency urinary incontinence?. Issue 9 (6th September 2014) - Gibson, W.; Athanasopoulos, A.; Goldman, H.; Madersbacher, H.; Newman, D.; Spinks, J.; Wyndaele, J. J.; Wagg, A.
Summary Overactive bladder and urgency incontinence are common and distressing conditions in older people, for which the first‐line pharmacological treatment is a bladder antimuscarinic agent. Of these, oxybutynin is often recommended in guidelines, but is associated with a higher incidence of adverse drug effects, and in particular has been suggested to have deleterious cognitive effects. Despite this, guidelines often suggest oxybutynin as first‐line treatment, and insurance based healthcare systems often require oxybutynin to be used as a first‐line therapy and fail before reimbursement for the cost of newer anticholinergics is authorised. We reviewed the literature of bladder antimuscarinics in older adults, using the headings overactive bladder, urinary frequency, urgency, urge, oxybutynin, antimuscarinic, older, older people, and frail. In general, oxybutynin had a similar efficacy to other anticholinergic drugs, but a higher incidence of adverse drug events, in particular significant yet unnoticed cognitive impairment. We conclude that oxybutynin should not be used in frail older people.